Rousseau Between Nature and Culture Philosophy, Literature, and Politics - Deneys-Tunney, Anne 1957-2017; Santos da Silva, Karen; Zarka, Yves Charles 1950- (Culture & Conflict, 2016)
Rousseau has been seen as the inventor of the concept of nature; in this collective volume philosophers and literary specialists from France and the United States examine how Rousseau's philosophy can be reinterpreted from the point of view of a constant dialectical debate between nature and culture. In this, Rousseau is our true contemporary